Automobile Driver Stress Detection By Wearable Glove System - D, Hepsiba.; D.Vijay Anand, L.; ., . (International Journal of Engineering and Technology, 2018)
This paper focuses on predicting the driver’s stress depending on the change in skin conductance. The Galvanic Skin Response (GSR) sensor is used for measuring the skin conductance. The electrical conductance varies with respect to the moisture of the skin produced by the sweat glands. The emotions of the driver such as normal state and stressed state are considered for monitoring. The electrical conductance of the skin helps to monitor the stress of the driver when driving the vehicle. Compared to other physiological signals such as ECG, EMG, EEG, EOG, Respiration Rate, this method is a simple and reliable method. Twenty subjects were exposed to the simulation driving environment under different scenarios such as  normal roads, highways and heavy traffic roads. The readings obtained from this study helps in detecting the driver’s stress level.